2014
DOI: 10.1007/s11745-014-3938-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes Controlling Unsaturated Fatty Acids Biosynthesis and Oil Deposition in Developing Seeds of Sacha Inchi (Plukenetia volubilis L.)

Abstract: Sacha inchi (Plukenetia volubilis L., Euphorbiaceae) seed oil is rich in α-linolenic acid, a kind of n-3 fatty acids with many health benefits. To discover the mechanism underlying α-linolenic acid accumulation in sacha inchi seeds, preliminary research on sacha inchi seed development was carried out from one week after fertilization until maturity, focusing on phenology, oil content, and lipid profiles. The results suggested that the development of sacha inchi seeds from pollination to mature seed could be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
3
12
1
Order By: Relevance
“…In the embryonic mature stage of flax seed, the genes encoding fatty acid desaturase in many isoforms were highly expressed 19 . Particularly, it had been reported that the expressions of the genes encoding sad, fad2, and fad3 were high, which was closely associated with the high production and accumulation of oil in storage cells of inca peanut 10 . These finding were also in good-agreement with the high expression of fad3 gene in perilla.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the embryonic mature stage of flax seed, the genes encoding fatty acid desaturase in many isoforms were highly expressed 19 . Particularly, it had been reported that the expressions of the genes encoding sad, fad2, and fad3 were high, which was closely associated with the high production and accumulation of oil in storage cells of inca peanut 10 . These finding were also in good-agreement with the high expression of fad3 gene in perilla.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a number of genes contributing to the production and accumulation of lipids are up-regulated. The transcriptome analysis of inca peanut seeds revealed that kas genes were highly expressed in middle-to-late stages during seed development, where the oil accumulation was beginning 10,20 . In flax seeds, kas genes were highly expressed at the middle stage of embryo development 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-temperature results in a higher unsaturation ratio (oleic/linoleic acid ratio) of fatty acids leading to decreased oil quality (Gibson and Mullen, 1996;Aksouh-Harradj et al, 2006). The temperature has been reported to modify the C-N metabolism and gaseous exchange favoring protein accumulation at the expense of oil and carbohydrates (Canvin, 1965;Wang and Liu, 2014). In B. napus, exposure to extremely low temperatures has also been shown to reduce photosynthetic efficiency and induce membrane damage leading to electrolyte leakage (Megha et al, 2018a).…”
Section: Physiological Impact Of Abiotic Stress In Canolamentioning
confidence: 99%